A numerical experiment for geological sequestration of CO2 in the pre-Comondú sandstones of Las Tres Virgenes geothermal area, Baja California Sur, Mexico. (March 2022) - Guerrero, Fernando J.; Pérez-Zárate, Daniel; Prol-Ledesma, Rosa Maria; Garza-Galindo, Rodrigo; Reyes-Sandoval, Alfonso; García-Zamorano, Eduardo A.
Highlights: A new perspective for geological sequestration of CO 2 in Mexican geologic settings. Assessment of geological sequestration of CO 2 in a tectonically active and high heat flow zone. Geological sequestration of CO 2 in high-temperature sandstone reservoir. Abstract: The most recent studies on geological sequestration of CO 2 in Mexico point towards high sequestration potential associated with geologically stable zones and high-emission centres. These studies overlook however, the potencial that high heat flow areas in the country can offer to geological sequestration of CO 2 by mineral precipitation. Here we present an assessment of the CO 2 sequestration capacity of the Pre-Comondú sandstones, that overlie the productive granitic basement of the Las Tres Virgenes geothermal field (10 MWe). Both, the physical properties and mineralogical description of the sandstone are defined from drilling core analyses reported by the Federal Commission of Electricity. The initial formation water saturating the sandstone is determined by means of a batch simulation of equilibrium between the primary minerals in the rock and a 1 M solution of NaCl in water. Injection of supercritical CO 2 is then numerically simulated. Simulations are based on the TOUGHREACT software and the equation of State Module ECO2N. Our results show Pre-Comondú sandstone favour mineralization of CO 2 through the precipitation of carbonates in moderate geologic times (100–300 yr). Mineral changes occur within two main zones in the CO 2 -impacted reservoir, the zone lying close to the injection point is dominated by precipitation of low-albite, kaolinite, calcite, and minor siderite, whereas the distal zone responds with moderate changes in the system illite-smectite. Changes in porosity are moderate and consistent with the two mineralization zones. Furthermore, the decline in porosity occurs in the long term, which suggests moderate risk for injection operations. Although high reservoir temperature is unfavorable to CO 2 solubility, high pressure can counteract this effect, so the system can benefit from higher mass diffusivity and reactivity. This manifests in an accelerated sequestration rate.